2018
DOI: 10.3390/jcm7040060
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward Nutrition Care among General Practitioners in Croatia

Abstract: Nutrition care should be an integral part of general practitioners’ (GPs’) daily work with patients. The aim of this study was to assess the attitudes of Croatian GPs toward nutrition and nutrition care, and to evaluate the interconnection between their attitudes and implementation of nutrition care in GPs offices. A cross-sectional study was conducted among 17.0% of randomly selected GPs, from May to July of 2013, via a specially designed anonymous questionnaire. The study showed that 36.0% of the Croatian GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 25 publications
(45 reference statements)
3
17
0
1
Order By: Relevance
“…Positive attitudes toward incorporating nutrition care in the management of patients living with diet-related chronic disease were found. This is consistent with other studies conducted around the world, which indicated that primary care physicians realise nutrition care as an important aspect of their clinical practice 14 19–21…”
Section: Discussionsupporting
confidence: 91%
“…Positive attitudes toward incorporating nutrition care in the management of patients living with diet-related chronic disease were found. This is consistent with other studies conducted around the world, which indicated that primary care physicians realise nutrition care as an important aspect of their clinical practice 14 19–21…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the personal ailment from chronic diseases and nutrition knowledge, it seems that Croatian GPs who have suffered from chronic diseases with improper nutrition posing as a risk factor, despite their illness, still do not recognize the significance of nutritional factors in their etiology. Such finding was also determined for the interconnection between the personal ailment from chronic diseases and attitudes toward the significance of nutrition in the treatment and prevention of chronic diseases and toward nutrition care among Croatian GPs [ 3 ]. GPs with poor nutrition knowledge that suffer from some kind of chronic diseases and despite that do not recognize the significance of nutritional factors in etiology of their diseases are bad role models for their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition care is an important component of healthcare that plays a critical role in the prevention and treatment of majority of chronic non-communicable diseases which are leading causes of morbidity and mortality throughout the world [ 1 , 2 ]. Nutrition care refers to any practice undertaken by a health professional to improve an individual’s food-related behavior and subsequent health outcomes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, respondents are prone to giving socially acceptable responses rather than giving their actual opinions. However, findings of self-reported studies are still considered to be as valid as more extensive and expensive tests [ 28 ].…”
Section: Discussionmentioning
confidence: 99%